2017
DOI: 10.1016/j.nedt.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of audio-visual storytelling in simulation learning experiences of undergraduate nursing students

Abstract: High satisfaction with simulation was indicated by all students in relation to value and realism. There was a significant finding in relation to transferability on knowledge and this is vital to quality educational outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…Beginner nursing students' satisfaction about simulation experiences presented high scores in both cases (MFS and HFS). Different authors have also reported high scores, supporting our findings regarding the students' satisfaction with both simulation methods [26,32,33,37]. The previous literature argues that this could be due to students forgetting disbelief before engaging in the task [38].…”
Section: Discussionsupporting
confidence: 89%
“…Beginner nursing students' satisfaction about simulation experiences presented high scores in both cases (MFS and HFS). Different authors have also reported high scores, supporting our findings regarding the students' satisfaction with both simulation methods [26,32,33,37]. The previous literature argues that this could be due to students forgetting disbelief before engaging in the task [38].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies with nursing students have shown that incorporation of an introductory video vignette using the manikin as a 'patient' resulted in the increased engagement of the students in subsequent encounters with the manikins that was characterized by a greater sense of connection and more understanding and empathy (Power et al, 2016;Johnston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Os melhores resultados se associaram uso de meios multimídias com áudio e imagem, promovendo o desenvolvimento de uma aprendizagem efetiva e consolidada, como visto nos estudos de Conlon et al (2020), Beck e Sitzman (2019), Urstad et al (2018), Johnston et al (2017), Scamell e Hanley (2017), Price et al (2015), Fenton (2014), Stacey e Hardy (2011), Christiansen (2011. Dessa forma, percebe-se que as narrativas digitais podem ser utilizadas para transformar o processo didático na enfermagem, com vistas a uma formação eficaz.…”
Section: Discussionunclassified